Regional right ventricular function in rats: a novel magnetic resonance imaging method for measurement of right ventricular strain - Espe, Emil K. S.; Aronsen, Jan M.; Nordén, Einar S.; Zhang, Lili; Sjaastad, Ivar (American journal of physiology. Heart and circulatory physiology, 2020)
The function of the right ventricle (RV) is linked to clinical outcome in many cardiovascular diseases, but its role in experimental heart failure remains largely unexplored due to difficulties in measuring RV function in vivo. We aimed to advance RV imaging by establishing phase-contrast MRI (PC-MRI) as a robust method for measuring RV function in rodents. A total of 46 Wistar-Hannover rats with left ventricular (LV) myocardial infarction and 10 control rats (sham) were examined 6 wk after surgery. Using a 9.4-T preclinical MRI system, we utilized PC-MRI to measure strain/strain rate in the RV free wall under isoflurane anesthesia. Cine MRI was used to measure RV volumes. LV end-diastolic pressure (LVEDP) was measured and used to identify pulmonary congestion. The infarct rats were divided into two groups: those with signs of pulmonary congestion (PC), with LVEDP ≥ 15 mmHg ( n = 26) and those without signs of pulmonary congestion (NPC), with LVEDP < 15 mmHg ( n = 20). The NPC rats exhibited preserved RV strains/strain rates, whereas the PC rats exhibited reduced strains/strain rates (26–48% lower than sham). Of the strain parameters, longitudinal strain and strain rate exhibited the highest correlations to LVEDP and lung weight (rho = 0.65–0.72, P < 0.001). Basal longitudinal strain was most closely associated with signs of pulmonary congestion and indexes of RV remodeling. Longitudinal RV strain had higher area under the curve than ejection fraction for detecting subtle RV dysfunction (area under the curve = 0.85 vs. 0.67). In conclusion, we show for the first time that global and regional RV myocardial strain can be measured robustly in rodents. Reduced RV strain was closely associated with indexes of pulmonary congestion and molecular markers of RV remodeling. NEW & NOTEWORTHY Global and regional right ventricular myocardial strain can be measured with high reproducibility and low interobserver variability in rodents using tissue phase mapping MRI. Reduced right ventricular strain was associated with indexes of pulmonary congestion and molecular markers of right ventricular remodeling. Regional strain in the basal myocardium was considerably higher than in the apical myocardium.